Radla’ah dan Implikasinya Perspektif Imam al-Nawawi dan Sayyid Sabiq - Muhamad Yusuf; Slamet Arofik (USRATUNA: Jurnal Hukum Keluarga Islam, 2026)
The study of raḍā‘ah (breastfeeding) occupies an important position in Islamic Family Law because it has implications for the establishment of maḥram relationships and marriage prohibitions. Although Islamic scholars generally agree that raḍā‘ah can produce legal consequences equivalent to those arising from blood kinship (nasab), differences of opinion remain regarding the criteria and limitations of breastfeeding that establish maḥram status. These differences have generated academic discourse concerning the relevance and application of raḍā‘ah law in contemporary society. This study aims to comparatively analyze the concept of raḍā‘ah according to Imam al-Nawawi and Sayyid Sabiq and to examine its implications for Islamic Family Law. This research employs a normative legal method with comparative and conceptual approaches. The data were obtained through library research on relevant primary and secondary sources and analyzed using a descriptive-analytical method. The findings reveal that both scholars agree that raḍā‘ah gives rise to a maḥram relationship that results in a prohibition of marriage. However, Imam al-Nawawi requires five separate breastfeeding sessions to establish such a relationship, whereas Sayyid Sabiq emphasizes breastfeeding that significantly contributes to a child’s growth without strictly limiting the number of feedings. These differences reflect variations in their methods of legal reasoning (istinbāṭ), although both ultimately pursue the same objectives of Islamic law: the preservation of lineage (ḥifẓ al-nasl), the protection of family honor, and the welfare of children.